Barriers and trust: Perceptions of the healthcare system among Roma mothers in Serbia - Pantović Ljiljana; Đorđević Ivan (Glasnik Etnografskog Instituta SANU)
This research aims to deepen the understanding of the barriers and challenges faced by Roma parents, particularly mothers, in accessing pediatric services in Serbia. The study found that distrust in the healthcare system, alongside cultural norms favoring traditional knowledge over medical advice, are key factors influencing Roma mothers’ healthcare decisions for their children. While pediatric services are generally perceived positively, significant infrastructural obstacles, especially in rural areas, hinder access to healthcare facilities. Special attention is given to the role of trust between healthcare workers and Roma mothers, with pediatricians often seen as crucial allies in safeguarding children’s health. The research highlights the need for improved communication and cultural sensitivity when working with the Roma community to foster greater trust in the healthcare system and enhance health outcomes for Roma families. Additionally, it underscores the importance of addressing structural inequalities that contribute to negative experiences.